Interstitial deletion of 3p22.3p22.2 encompassing ARPP21 and CLASP2 is a potential pathogenic factor for a syndromic form of intellectual disability: A co‐morbidity model with additional copy number variations in a large family. Issue 11 (11th October 2013) - Marangi, Giuseppe; Orteschi, Daniela; Milano, Valentina; Mancano, Giorgia; Zollino, Marcella
ABSTRACT We describe a family in which four individuals (the mother and three children) presented with an overlapping phenotype of minor physical anomalies and intellectual disability. Four previously unreported copy number variants were found inherited either from the affected mother or from the healthy father, consisting of a 3p22.3p22.2 deletion (2.5 Mb), a 3p24.3 deletion (0.55 Mb), a 6q22.31 duplication (0.74 Mb), all maternally inherited, and an 18q11.2 duplication (0.276 Mb) which was paternally inherited. The deletions on chromosome 3 were both found to segregate with the disease. However, being the 0.55 Mb deleted segment on 3p24.3 devoid of genes, we considered that the 2.5 Mb deletion on 3p22.3p22.2 acts as major pathogenic rearrangement in this condition. Among the transcribed genes residing in this interval, ARPP21 and CLASP2 are proposed as good candidate genes on the basis of their functional properties. A co‐morbidity role for the other small rearrangements detected in the affected individuals in association with the 3p22.3p22.2 deletion is also suggested, according to a second‐side model of pathogenesis. © 2013 Wiley Periodicals, Inc.